MILLS’ PERSPECTIVE ON SIMA BAHOUS CLOSING SPEECH AT UN-WOMEN ANNUAL SEASON: A FEMINIST CRITICAL DISCOURSE ANALYSIS - Muthi'ah, Nadhirah; Frida, Karunia Devy; Zein, T. Thyrhaya (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2023)
The study aimed to find out the women's representation of Sima Bahous' speech entitled "Looking Forward to a Future of Gender Equality" by applying Mills' discourse analysis perspective, such as the subject-object position, reader position, and writer-reader position. The presence of the UN Women organization is a new step and a source of hope for women fighting for gender equality and women's empowerment. Sima Bahous, the woman behind UN Women, contributed to improving the position of women globally through her speech. The descriptive qualitative method was employed in the research supported by  the theory of critical discourse analysis with a feminist perspective by Sara Mills. The result showed that in Sima Bahous' selected closing remarks speech, the position of the subject was placed by Sima Bahous as the speaker of her speech and UN Women as the object of the speech. The listener's position was related to the greeting to the listener. Through "mediation" and "cultural codes," this was achieved in a circumstantial manner.